Teologi Toleransi menurut Hans Kung dan Abdurrahman Wahid - Irfany, Muhammad Rifky (Jurnal Riset Agama, 2023)
The problem of intolerance in Indonesia is increasing as evidenced by the results of the SETARA Institute survey, which has increased to 8% in 2020. This is due to the distant understanding of religion which is then wrapped up by the politicization of religion. To answer this problem, a deeper understanding of theology is needed. Therefore, the researcher conducted research with a qualitative descriptive approach through a comparative study to describe these thoughts. After conducting research, it was found that the theological thoughts of Hans Kung and Abdurrahman Wahid both emphasized the importance of dialogue as a basis for mutual understanding, both the teachings of one's own religion and the religions and beliefs of others. The theory used is the theory of Ecumenical Theology (the important thing is the understanding of a religion that cannot be understood only by adherents of that religion but also by people outside the religion) and also Pluralism (the attitude of religious beliefs is the most correct but does not then blame religion or other beliefs).